Contribution of Outbound Activities to the Soft Skills of Management Osis and MPK at SMAN 3 Kupang City - Maria Andriani Barek Ladjar; Veramyta Maria Martha Flora Babang; Jurdan Martin Siahaan (UNIB Press, 2023)
Soft Skill is a important factor in a organization. Soft skill who someone have can show ability to preparing him/herslef agains thread of the world. OSIS and MPK committee’s are role model from indiviual who have soft skill and hard skill. They are selected among student who have capability to do task as OSIS and MPK committee’s. There are many way to develop soft skill capability, among them; attended a training/seminar, attended a indoor training and outdoor training. One of the outdoor training is outbound activity. Outbound activities are packaged in the form of interesting games, but a lot of soft skills will be obtained from each game that is followed. This research goals to analyze the contribution of outbound activities to the soft skills of OSIS and MPK administrators at SMAN 3 Kota Kupang. The research sample consisted of 22 members of the OSIS and MPK committee at SMAN 3 Kota Kupang. The research design used is the One Group Pre-Post Test Design. According to the results of the regression test, an F value of 4.644 was obtained with a Sig. 0.044 <0.05, then outbound activities contribute to the soft skills of OSIS and MPK administrators at SMAN 3 Kota Kupang. The coefficient of determination (R Square) is 0.188 which means that the contribution of the independent variable (outbound activities) to the dependent variable (soft skills) is 18.8%. Therefore, it is recommended that OSIS and MPK coaches make outbound activities an alternative in improving the soft skills of OSIS and MPK administrators.